2019
DOI: 10.5152/tjar.2015.89410
|View full text |Cite
|
Sign up to set email alerts
|

Colostomy with Transversus Abdominis Plane Block

Abstract: Case ReportTransversus abdominis plane (TAP) block is one of the abdominal field block. The TAP block is used for both anaesthetic management and post-operative pain therapy in lower abdominal surgery. TAP block is a procedure in which local anaesthetic agents are applied to the anatomic neurofacial space between the internal oblique and the transversus abdominis muscle. TAP block is a good method for post-operative pain control as well as allows for short operations involving the abdominal area. In this artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
2
0
3
Order By: Relevance
“…In recent years, ultrasoundguided TAP block has gained popularity for intraoperative and postoperative pain management in pediatrics 10,11 . Tekelioğlu et al, emphasized that, in short interventions involving the abdominal region via colostomy with mild sedation and TAP block, ultrasound-guided TAP block has provided opportunity for an effective and reliable surgery accompanied by sedation and also long-term postoperative pain control 8 . Also in the study conducted by Alsadek et al,to compare the caudal block and TAP block, they observed that HR and MAP were always higher in the group without block; however, this difference was not significant 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, ultrasoundguided TAP block has gained popularity for intraoperative and postoperative pain management in pediatrics 10,11 . Tekelioğlu et al, emphasized that, in short interventions involving the abdominal region via colostomy with mild sedation and TAP block, ultrasound-guided TAP block has provided opportunity for an effective and reliable surgery accompanied by sedation and also long-term postoperative pain control 8 . Also in the study conducted by Alsadek et al,to compare the caudal block and TAP block, they observed that HR and MAP were always higher in the group without block; however, this difference was not significant 9 .…”
Section: Discussionmentioning
confidence: 99%
“…TAP block is a good method in postoperative pain control and also provides opportunity for short interventions related to the abdominal region 3 . As specified in the literature, TAP block application [4][5][6][7] that is most frequently used for postoperative analgesia purpose is also used to provide anesthesia although rare 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonografi yöntemi ile birlikte daha güvenli ve etkili bir uygulama haline gelen TAP blok, literatürde birçok durumda kullanılmaktadır (7) . TAP bloğu, fıtık onarımı, sezaryen, abdominal histerektomi ve prostatektomi, apendektomi gibi alt abdominal alanı ilgilendiren cerrahi girişimlerde kullanılabilir.…”
Section: Transversus Abdominis Plan Bloğun Uygulama Alanlarıunclassified
“…Laparoskopik kolorektal cerrahi sonrası TAP blok uygulanan hastalarda morfin tüketiminin anlamlı olarak düşük bulunduğu bildirilmiştir (15) . Genel durumu kötü, ileri derece organ yetersizliği olan, genel anestezi ve santral blokların uygulanamadığı hastalarda, abdominal bölgeyi ile ilgili kısa cerrahi uygulamalarda, ultrasonografi ve sedasyon eşliğinde uygulanan TAP bloğun hem etkili ve güvenilir bir cerrahiye hem de ameliyat sonrası dönemde ağrı kontrolünü sağladığı yapılan çalışmalarla vurgulanmıştır (7) . varlığı ve pıhtılaşma bozukluğu kontrendikasyon olarak kabul edilmektedir (12) .…”
Section: Transversus Abdominis Plan Bloğun Uygulama Alanlarıunclassified
See 1 more Smart Citation